Pengaruh Gaya Kepemimpinan, Komunikasi, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. PLTD Persero Sapudi Madura - Maimun, Muhammad; Rizal, Mohammad; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted at PT. PLTD Persero Sapudi Madura. This study aims to determine the effect of leadership style, communication, motivation and work discipline on employee performance. The type of research used is quantitative research. Primary data sources were obtained from questionnaire data measured using a Likert scale. The population in this study were employees of PT. PLTD Persero Sapudi Madura totaling 50 employees, then the number of samples was taken using the saturated sampling method. The results of this study indicate that 1) Leadership style, communication, motivation and work discipline simultaneously affect the performance of employees of PT. PLTD Persero Sapudi Madura. 2) Leadership style has a positive and significant effect on the performance of employees of PT. PLTD Persero Sapudi Madura. 3) Communication has a positive and significant effect on the performance of employees of PT. PLTD Persero Sapudi Madura. 4) Motivation does not have a significant effect on the performance of employees of PT. PLTD Persero Sapudi Madura. 5) Work discipline has a positive and significant effect on the performance of employees of PT. PLTD Persero Sapudi Madura. Keywords: Leadership Style, Communication, Motivation, Work Discipline, Employee Performance